Energy analysis of magnetite nanofluid flowing in newly designed sudden expansion tube retrofitted with dimpled fin - Gürsoy, Emrehan; Kadir Pazarlıoğlu, Hayati; Dağdeviren, Abdullah; Gürdal, Mehmet; Gedik, Engin; Arslan, Kamil; Kurt, Hüseyin (Elsevier BV, 2022)
Sudden expansion geometry plays an important role in the design of many engineering applications such as heat exchangers to avoid thermal stress on welded joints. While the heat transfer in these geometries is maximized at the reattachment points, it decreases to a minimum in the recirculation regions created by the fluid. To prevent this situation and improve the performance of the expansion tubes, nanofluid, and expanded surfaces can be used. For this purpose, forced convection of magnetite nanofluid flow in various expansion ratios has been investigated numerically in this study. Analyses have been performed on Reynolds (Re) numbers ranging from 100 to 2000, constant and uniform heat flux at 600 W/m2, and volume concentrations (1.0≤φ≤2.0 vol.%). The result showed that while the Nu number increases with increasing Re number, the most efficient case is Dimpled Tube (DT) 9, and the highest value of performance evaluation criteria (PEC) has been obtained at φ=2.0 vol.%. Compared with the water, the highest Nu number value has been obtained as 3.34% increased at Re=2000 and φ=2.0 vol.%. When compared to the DT9 and Smooth Tube (ST) 1 where water was used as the working fluid at Re=2000 and φ=2.0 vol.%, the PEC value increased by 8.66% and 110.31%, respectively. In addition, the bottom wall of the DT9 case performs higher convective heat transfer rate than the top wall.
Keywords: 7. Clean energy